2016
DOI: 10.1080/10401334.2016.1202832
|View full text |Cite
|
Sign up to set email alerts
|

Cheating in OSCEs: The Impact of Simulated Security Breaches on OSCE Performance

Abstract: This simulation of different OSCE security breaches demonstrated that student performance is greatly advantaged by having prior access to test materials. This has important implications for medical educators as they develop policies and procedures regarding the safeguarding and reuse of test content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Pragmatically, our results suggest that using a question three times or more within a short time span (5 years) can impact the question’s psychometric properties. Pooling questions from different institutions could be an interesting way to increase item-bank size and thus access to questions with known psychometric properties, while limiting the re-use of a specific question within a short time span, as also suggested by Gotzman and colleagues [ 15 ]. Gierl and colleagues [ 32 35 ] have also proposed, and demonstrated, the potential for automated item generation which could reduce the burden on exam developers to create new questions each year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pragmatically, our results suggest that using a question three times or more within a short time span (5 years) can impact the question’s psychometric properties. Pooling questions from different institutions could be an interesting way to increase item-bank size and thus access to questions with known psychometric properties, while limiting the re-use of a specific question within a short time span, as also suggested by Gotzman and colleagues [ 15 ]. Gierl and colleagues [ 32 35 ] have also proposed, and demonstrated, the potential for automated item generation which could reduce the burden on exam developers to create new questions each year.…”
Section: Discussionmentioning
confidence: 99%
“…The known use of banked items in assessment often leads to strategies such as content sharing [ 12 – 14 ]—between trainees—and are an unfortunate reality in medical education [ 14 ]. Content sharing goes beyond the context of written exams to also be observed in the context of performance-based assessment [ 15 ] and is per definition detrimental to the validity of assessment data interpretation [ 16 ]. Unfortunately, self-reports for cheating behaviours range from 5 to 94% of students adopting some sort of cheating behaviours [ 14 , 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small number of long-term studies Jolly et al 1993) have shown evidence of progressive improvement in OSCE scores when the same stations are repeated over consecutive years. Gotzmann et al (2017) demonstrated an improvement in overall total scores in an artificially breached test security setting where two cohorts of students were given information about the stations beforehand.…”
Section: Introductionmentioning
confidence: 98%
“…The increasingly innovative communication methods, coupled with the absence of a physical holding area to invigilate students, increase the likelihood of collusion and cheating among students during online OSCEs. Students who undertake the OSCE later in the examination schedule may have an unfair advantage due to the potential sharing of examination information by those who have already completed the OSCE (Gotzmann et al, 2017;Ghouri et al, 2018;Noonan et al, 2020). Although anecdotal evidence shows that inadvertent exposure of examination materials to students prior to the OSCE (Wilkinson et al, 2003) or collusion among students during OSCE (Parks et al, 2006) does not always translate to higher marks in the 'advantaged' group of students, such breaches of academic integrity undeniably undermine the quality of the assessment.…”
Section: Introductionmentioning
confidence: 99%